The Combination of suprakeloidal flap and pulsed light heat energy in keloid management: a Case report - Dwi retno Adiwinarni, Yohanes Widodo Wirohadidjojo Kristiana Etnawati (Universitas Gadjah Mada, 2008)
The role of chronic tissue hypoxia in the keloid patho-mechanism has been widely accepted. Whereas, the pulsed-light heat energy (LHE) has been developed which has the capacity to generate reactive oxygen species on exposed skin. Although the supra keloidal flap technique has a high recurrence rate, it was used because of its capacity to prevent suturing hypoxia, thereby the formation of lager recurrent keloid after surgery.The combination of supra keloidal flap and pulsed light heat energy was done I the treatment of postvaricella keloid on the right ear lobe of a 9 year old girl. The keloid was excised two times a year ago, but observation one month after the surgery showed a recurrent larger keloid. The performance of supra keloidal technique followed by pulsed-light heat energy treatment in dose 2.5 J/cm2, was administered on day 3r